(untitled) (Web of Teachers: Inderscience Research, 2024)
This Article Presents the Results of Research on the Properties of the Nervous System of Highly Qualified Boxers, Analyzes the Patterns of Connections Between Psychophysiological Characteristics and The Individual Style of Activity of Boxers.